The Role of the Government in Increasing Community Welfare in Pohuwato Regency - Edy Sijaya (Jurnal Ad'ministrare, 2019)
This research aims to determine the role of the village government in improving the welfare of the people of Bulili Village in Duhiadaa District, Pohuwato Regency. The research approach uses descriptive research which provides an overview of how the government plays a role in improving the welfare of the community in the village of Bulili, Duhiadaa District, Pohuwato Regency. Informants were the village head, village head, BPD chairman, LPM Chair, village treasurer and Bulili village community leaders. The results showed that the Bulili Village Government in improving community welfare carried out three programs such as: 1) agricultural production improvement program. For the economic sector the Bulili village government planned assistance that would improve the economy of Bulili villagers such as providing rice seeds, corn seeds, tractor assistance, Hansplayer (tengki) assistance, fertilizer assistance, and PNPM assistance, 2) program to increase livestock production, namely the collaboration of district government, sub-district government and Bulili village government in the form of providing assistance for productive superior cows and productive goat seeds to village community livestock farmers bulili which was formed by the village village government. 3) development of village livestock agribusiness, which is to form a group of livestock farmers who are given the assistance of productive cow and goat seeds to each group to be managed as part of a government program in order to improve the welfare of the village community. In addition, the formation of livestock farmer groups is one of the right solutions in increasing livestock business in the village, various livestock businesses such as the procurement of productive seeds, prevention of livestock diseases and access to marketing can be done in groups and work together which in turn increases profits and business income in order to improve the welfare of the people in Bulili village.